STUDENTS’ PERCEPTION TOWARD THEIR READING DIFFICULTIES OF DIFFERENT GENRES - Sari, Rima Andriani (English Department FBS UNP, 2013)
Students of English Language Teaching Program are required to have the ability to comprehend different kinds of texts or genres. Howewer, their reading ability as reflected in Reading courses and other courses is low. This paper is aimed at describing the students’ perception toward their reading difficulties of different genres. The data presented in this paper are partially derived from the data collected through a descriptive research conducted in 2009/2010 at the English Department of FBSS, State University of Padang. The instrument of the research were a reading test, which was to determine the level of the students in genre awareness and reading comprehension, and interview to gain students’ perception on their reading difficulties. Data were analysed descriptive-qualitatively and descriptive-quantitatively. From the result of the test, the students thus are categorised into high, middle and low achievers. The result of the interview showed that students with different level of comprehension had different difficulties in understanding texts with different genres because of some factors. Thus, improving the syllabus on Reading courses and other related courses such as Writing, TEFL dan Linguistics are considered important. Keywords: perception, genre awareness, reading comprehension